Potential Impact of Substituents on the Crystal Structures and Properties of Tl(I) Ferrocenyl/Picolyl‐Functionalized Dithiocarbamates; Tl⋯H‐CAnagostic Interactions. Issue 18 (14th November 2016) - Manar, Krishna K.; Rajput, Gunjan; Yadav, Manoj K.; Yadav, Chote L.; Kumari, Kavita; Drew, Michael G. B.; Singh, Nanhai
Abstract: New ferrocenyl/pyridyl functionalized dithiocarbamate complexes, [Tl(dtc)]∞ (dtc=(N‐ferrocenyl‐N‐2‐methylpyridyl) dithiocarbamate (L1)1, (N‐ferrocenyl‐N‐methyl) dithiocarbamate (L2)2, (N‐methylthiophene‐N‐3‐methylpyridyl) dithiocarbamate (L3)3, (N‐4‐chlorobenzyl‐N‐3‐methylpyridyl) dithiocarbamate (L4)4 and (N‐4‐methylbenzyl‐N‐3‐methylpyridyl) dithiocarbamate (L5)5 ) have been synthesized and characterized by elemental analyses, IR, UV‐Vis., 1 H and 13 C { 1 H} NMR spectroscopy. Their crystal structures revealed polymeric structures based on dimeric [Tl(dtc)]2 scaffolds which are linked via Tl⋯Tl, Tl‐N(Py) and Tl⋯S bonds and rare C−H⋯Tl anagostic, C–S⋯Tl, Tl⋯N(dtc), Tl⋯C and Tl⋯π(arene) intermolecular bonding interactions which have been assessed by theoretical calculations.The supramolecular structures in these complexes have been sustained by weak C−H⋯S, C−H⋯N, C−H⋯Cl, C−H⋯π, π⋯ π and H⋯H interactions. Except for1 and2 having ferrocene groups as quenchers, all the complexes show luminescent characteristics in the solid phase. Complexes1–5 are weakly conducting (σrt, 10 −4 ‐10 −7 S cm −1, Ea=0.89‐1.00 eV) but show semiconducting behavior in the solid state. The TGA decomposition products of1—5 revealed formation of binary TlS and ternary Fe2 Tl4 S5 and Fe3 Tl2 S4 sulfide materials. Abstract : Influence of ferrocenyl/picolyl functionalities on the structure and properties of [Tl(dtc)]∞ (dtc=(N‐ferrocenyl‐N‐2‐methylpyridyl) dithiocarbamate (L1)1, (N‐ferrocenyl‐N‐methyl) dithiocarbamate (L2)2, (N‐methylthiophene‐N‐3‐methylpyridyl) dithiocarbamate (L3)3, (N‐4‐chlorobenzyl‐N‐3‐methylpyridyl) dithiocarbamate (L4)4 and (N‐4‐methylbenzyl‐N‐3‐methylpyridyl) dithiocarbamate (L5)5 ). X‐ray crystal structures revealed existence of rare C−H⋯Tl intermolecular anagostic, Tl⋯N(dtc), Tl⋯π(arene) and C−S⋯Tl interactions in these complexes which have been supported by theoretical calculations. They show luminescent and solid phase conducting characteristics.